Online Classrooms in the Digital Era - Online Presence Through Learners’ Perception - Duy, Pham Khanh; Hiep, Pham Cong (VNU Journal of Science: Education Research, 2022)
This research aims to evaluate learners’ experience of online presence (i.e., teaching, social, cognitive presence) on learning needs, outcomes and challenges in meeting those expectations at a Vietnam university, which offered an entire curriculum online during 2020 and 2021 in response to a strict social distancing mandate. This study provides the following contributions. First, it helps educational institutions understand online learners’ pressing needs using a well-studied framework and create a high-level, engaging online learning environment. Second, it complements other studies that examine the Community of Inquiry framework in the context of a university in Vietnam during COVID-19, whose findings can be generalizable to other institutions. Finally, it puts forward further challenges that educational institutions should consider balancing online learners’ needs and operational constraints to advance the effectiveness of online learning. The study shows that the students highly regarded teaching presence from the instructors and institution, which included online infrastructure, learning management system, and various online teaching modes. Lively online lectures, recorded sessions, and the use of social media made the learning experience satisfactory. However, cognitive and social presence was not found strongly present in students’ learning. Class sizes, workload, and lack of personal contacts were found to be the main reasons for instructors not promoting such aspects of the learning.